Computational study of nitro-benzylidene phenazine as dengue virus-2 NS2B-NS3 protease inhibitor - Salin, Nurul Hanim; Hariono, Maywan; Khalili, Nur Sarah Dyana; Zakaria, Iffah Izzati; Saqallah, Fadi G.; Mohamad Taib, Mohamad Nurul Azmi; Kamarulzaman, Ezatul Ezleen; Wahab, Habibah A.; Khawory, Muhammad Hidhir (Frontiers in Molecular Biosciences, 2022)
According to the World Health Organisation (WHO), as of week 23 of 2022, there were more than 1,311 cases of dengue in Malaysia, with 13 deaths reported. Furthermore, there was an increase of 65.7% during the same period in 2021. Despite the increase in cumulative dengue incidence, there is no effective antiviral drug available for dengue treatment. This work aimed to evaluate several nitro-benzylidene phenazine compounds, especially those that contain 4-hydroxy-3,5-bis((2-(4-nitrophenyl)hydrazinylidene)-methyl)benzoate through pharmacophore queries selection method as potential dengue virus 2 (DENV2) NS2B-NS3 protease inhibitors. Herein, molecular docking was employed to correlate the energies of selected hits’ free binding and their binding affinities. Pan assay interference compounds (PAINS) filter was also adopted to identify and assess the drug-likeness, toxicity, mutagenicity potentials, and pharmacokinetic profiles to select hit compounds that can be considered as lead DENV2 NS2B-NS3 protease inhibitors. Molecular dynamics assessment of two nitro-benzylidene phenazine derivatives bearing dinitro and hydroxy groups at the benzylidene ring showed their stability at the main binding pocket of DENV2 protease, where their MM-PBSA binding energies were between -22.53 and -17.01 kcal/mol. This work reports those two nitro-benzylidene phenazine derivatives as hits with 52–55% efficiency as antiviral candidates. Therefore, further optimisation is required to minimise the lead compounds’ toxicity and mutagenicity.